Asuhan Keperawatan Lansia Diabetes Melitus Tipe 2 Dengan Masalah Keletihan Di Kota Palu - Nova Natalia Beba; Monika Pretty; Juliana Neng Rifka Sarman (Nursing Practice Journal, 2025)
Diabetes mellitus is a chronic metabolic disease or disorder caused by various etiologies. This disease is characterized by high blood glucose levels and impaired carbohydrate, lipid, and protein metabolism due to functional insufficiency. In patients with type 2 diabetes mellitus, fatigue is one of the symptoms of physiological processes, treatment procedures, and complications that diabetes mellitus sufferers often experience in the long term. Energy management is a structured strategy to help diabetes mellitus sufferers manage and optimize their energy use, thereby reducing fatigue. This study aims to describe nursing care for elderly people with type 2 diabetes mellitus with fatigue nursing problems in Palu City, Central Sulawesi Province. This study uses a descriptive case study method. Data collection methods included interviews, observations, and assessments. The instruments used are general assessments and assessments of fatigue measurement scales. The results showed that fatigue problems were found to be related to physiological conditions (diabetes mellitus) in accordance with the signs and symptoms of the Indonesian Nursing Diagnosis Standards (SDKI). The interventions provided were 11 interventions according to the Indonesian nursing intervention standards (SIKI). After five nursing care sessions, the fatigue assessment scale showed a decrease. It is hoped that the results of this case study will enable respondents to implement daily energy management activities to address fatigue in patients with Type 2 Diabetes Mellitus.